Association of handgrip strength asymmetry and weakness with successful aging among older adults in China - Wei Ji; Yanping Wang; Chunping Ni; Xueyan Huang; Wenjuan He (PLoS ONE, 2026)
Background Successful aging (SA) is important for the increasing population aging. The role of handgrip strength(HGS) asymmetry and weakness in successful aging requires further clarification. This study aimed to elucidate the association of HGS asymmetry and weakness with successful aging in older adults. Methods We included participants aged ≥60 years from the 2015 China Health and Retirement Longitudinal Study (CHARLS).SA absence of major diseases, absence of major chronic diseases, no impairment in physical function, high cognitive functioning, good mental health, and active participation in life. HGS asymmetry and weakness were measured using the maximum value of the HGS. Logistic regression modeling was used to examine the association of individuals with HGS asymmetry and weakness with SA. Restricted cubic spline (RCS) modeling was used to explore potential nonlinear relationships. Results Of the 5,031 individuals included, the median age of the study population was 67 years IQR: 63−73 years, 45.6% female. Only 6.3% met the criteria for successful aging. HGS asymmetry (OR = 0.597,95% CI: 0.472–0.754) and weakness (OR = 0.643,95% CI: 0.417–0.964) were both independent influences on SA. Participants were less likely to have SA when both HGD asymmetry and weakness were present (OR = 0.426,95% CI: 0.240–0.757). Further subgroup analyses revealed significant associations between HGS status and each of the components of SA, particularly with regard to physical functioning. There was an inverse U-shaped relationship between HGS asymmetry and SA. Conclusion HGS asymmetry is associated with a reduced likelihood of weak SA. Improving or maintaining HGS symmetry and weakness may contribute to SA in older adults.